Technologická etapa hrubé spodní stavby OÚ Ostrá - Kholodniak, Marko (Vysoké učení technické v Brně. Fakulta stavební, 2024)
Bakalářka práce je zaměřená na realizaci a rekonstrukci spodní hrubé stavby obecního úřadu v Ostré. Původní objekt má jedno podzemní podlaží, jedno nadzemní a neobytnou půdu. Objekt je založeny plošným způsobem na základových pásech, svislé nosné konstrukce jsou tvořené z cihel plných pálených, vodorovné nosné nad 1.PP jsou tvořené monolitickým trámovým stropem a ŽB deskou doplněnou ocelovým průvlakem. Přístavba bude mít jedno nadzemní podlaží a jedno podzemní. Přístavba bude založená na základové desce doplněnou základovými pasy po obvodě základové desky, které však nebudou mít nosnou funkci. Svislé nosné konstrukce budou řešené kompletně systémem POROTHERM, strop nad 1. PP přístavby bude ŽB monolitický. Práce obsahuje technickou zprávu se zaměřením na vybranou technologickou etapu, situaci stavby se širšími dopravními vztahy dopravních tras, výkaz výměr, technologický předpis pro realizaci základových konstrukci, výkres a zprávu zařízení staveniště, časový plán, návrh strojní sestavy, kontrolní a zkušební plán pro realizaci základových konstrukci, bezpečnost a ochranu zdraví při prací.

The bachelor's thesis is focused on the implementation and reconstruction of the lower gross structure of the municipal office in Ostrá. The original building has one underground floor, one above ground floor and a non-residential floor. The building is based in a flat manner on the foundation strips, the vertical load-bearing structures are made of full-burnt bricks, the horizontal load-bearing structures above the 1.PP are formed by a monolithic beam ceiling and a reinforced concrete slab supplemented with a steel beam. The extension will have one above-ground floor and one underground floor. The extension will be based on a base plate supplemented with foundation belts around the perimeter of the base plate, which, however, will not have a load-bearing function. The vertical supporting structures will be completely covered with the POROTHERM system, the ceiling above the 1st PP extension will be ŽB monolithic. The work contains a technical report with a focus on the selected technological stage, the situation of the building with wider traffic relations of the transport routes, a list of measures, a technological regulation for the implementation of foundation structures, a drawing and report of the construction site equipment, a time schedule, a design of the machine assembly, an inspection and test plan for the implementation of the foundation construction, safety and health protection at work.
The technological stage of the rough substructure of OÚ Ostrá
Keywords: Hrubá spodní stavba; rekonstrukce; přístavba; základová deska; základové pásy; zesílení stávající konstrukci; základové patky; výztuž; tradiční bednění; systémové bednění; monolitický strop; hydroizolace; technologický předpis; kontrolní a zkušební plán; zařízení staveniště; strojní sestava; bezpečnost a ochrana zdraví.; Gross substructure; reconstruction; extension; foundation slab; foundation strips; reinforcement of existing structure; foundation feet; reinforcement; traditional formwork; system formwork; monolithic ceiling; waterproofing; technological regulation; inspection and test plan; construction site equipment; machinery assembly; safety and health protection.